2009
DOI: 10.1007/s10803-009-0884-3
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition in Children with Autism Spectrum Disorders: Relations to Eye Gaze and Autonomic State

Abstract: Respiratory Sinus Arrhythmia (RSA), heart rate, and accuracy and latency of emotion recognition were evaluated in children with autism spectrum disorders (ASD) and typically developing children while viewing videos of faces slowly transitioning from a neutral expression to one of six basic emotions (e.g., anger, disgust, fear, happiness, sadness, and surprise). Children with ASD were slower in emotion recognition and selectively made more errors in detecting anger. ASD children had lower amplitude RSA and fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
383
5
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 497 publications
(445 citation statements)
references
References 59 publications
45
383
5
12
Order By: Relevance
“…Finally, the authors reviewed these 168 articles in a more in-depth review and reached a consensus to further exclude 136 articles (70 did not involve participants with an ASD diagnosis, 42 were theoretical papers or secondary reviews, 15 did not include at least one ER measure, and 9 did not involve participants with an ASD diagnosis and were theoretical papers or secondary reviews), resulting in 32 articles that met the criteria and were included in the current review. Reference lists from the 32 studies were also reviewed [see asterisks in reference list for final included studies; specifically, three were ultimately identified through Bal et al, 2010;Mazefsky et al, 2013;Sofronoff, Attwood, Hinton, & Levin, 2007;Van Hecke et al, 2009].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the authors reviewed these 168 articles in a more in-depth review and reached a consensus to further exclude 136 articles (70 did not involve participants with an ASD diagnosis, 42 were theoretical papers or secondary reviews, 15 did not include at least one ER measure, and 9 did not involve participants with an ASD diagnosis and were theoretical papers or secondary reviews), resulting in 32 articles that met the criteria and were included in the current review. Reference lists from the 32 studies were also reviewed [see asterisks in reference list for final included studies; specifically, three were ultimately identified through Bal et al, 2010;Mazefsky et al, 2013;Sofronoff, Attwood, Hinton, & Levin, 2007;Van Hecke et al, 2009].…”
Section: Methodsmentioning
confidence: 99%
“…The Sinus Arrhythmia/Heart Rate measure was used in three of the four studies [Bal et al, 2010;Neuhaus, Bernier, & Beauchaine, 2014;Van Hecke et al, 2009], and the remaining three measures were each used in only one of Inter-rater reliability κ = 0.81-1.0 ER strategies coded in 10-second intervals √ Facial or bodily negativity [Ekman & Friesen, 1978] Jahromi et al Interrater reliability,…”
Section: Methods Of Measurementmentioning
confidence: 99%
See 3 more Smart Citations